1999
DOI: 10.1128/cmr.12.1.147
|View full text |Cite|
|
Sign up to set email alerts
|

Antiseptics and Disinfectants: Activity, Action, and Resistance

Abstract: SUMMARY Antiseptics and disinfectants are extensively used in hospitals and other health care settings for a variety of topical and hard-surface applications. A wide variety of active chemical agents (biocides) are found in these products, many of which have been used for hundreds of years, including alcohols, phenols, iodine, and chlorine. Most of these active agents demonstrate broad-spectrum antimicrobial activity; however, little is known about the mode of action of these agents in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
2,732
3
131

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,916 publications
(3,071 citation statements)
references
References 461 publications
46
2,732
3
131
Order By: Relevance
“…Previous research has also demonstrated that photoirradiated TiO 2 catalyzed site-specific DNA damage by generating H 2 O 2 (Hirakawa et al 2004). These findings suggested that TiO 2 might exert similar antimicrobial effects to those of the disinfectant H 2 O 2 (McDonnell and Russell 1999). The oxidation of bacterial cell components, such as lipids and DNA, might, therefore, result in subsequent cell death (Maness et al 1999).…”
Section: Introductionmentioning
confidence: 85%
“…Previous research has also demonstrated that photoirradiated TiO 2 catalyzed site-specific DNA damage by generating H 2 O 2 (Hirakawa et al 2004). These findings suggested that TiO 2 might exert similar antimicrobial effects to those of the disinfectant H 2 O 2 (McDonnell and Russell 1999). The oxidation of bacterial cell components, such as lipids and DNA, might, therefore, result in subsequent cell death (Maness et al 1999).…”
Section: Introductionmentioning
confidence: 85%
“…Consequently, the development of highly efficient and low-cost antibacterial surfaces has been the object of many research works [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…[91]. Eine Selektion von Bakterien mit Antibiotikaresistenzen bei Einsatz von richtig durchgeführten Flächendesinfekti-onsverfahren ist bislang nicht beobachtet worden [92,93,94,95].…”
Section: Häufigkeit Von Reinigung Bzw Desinfektion In Unterschiedlicunclassified